Dr. Catherine Xue — Deep Plane Facelift — Shanghai - Xue, Catherine (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Catherine Xue, practicing in Shanghai, China. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003353; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; china; shanghai